2018
DOI: 10.1021/acsami.7b17233
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Liquid Metal As a Transformable Biomimetic Chameleon

Abstract: Liquid metal (LM) is of core interest for a wide variety of newly emerging areas. However, the functional materials thus made so far by LM only could display a single silver-white appearance. In this study, colorful LM marbles working like a transformable biomimetic robot were proposed for the first time and fabricated from LM droplets through encasing them with fluorescent nanoparticles. We demonstrated that this unique LM marble can be manipulated into various stable magnificent appearances as one desires an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 50 publications
0
66
0
Order By: Relevance
“…1 E), which indicating a reduction of Au ions and presence of Au NPs. This phenomenon was benefited from the interfacial galvanic replacement reaction contributed by Ga and Au ions [ [45] , [46] , [47] ]. SEM images ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 E), which indicating a reduction of Au ions and presence of Au NPs. This phenomenon was benefited from the interfacial galvanic replacement reaction contributed by Ga and Au ions [ [45] , [46] , [47] ]. SEM images ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[59] And Shuting Liang et al demonstrated a liquid metal marble splitting and merging among different colors. [60] Therefore, the MCLMMs to work in a much more complex air-liquid environment and possess more functions can be still studied in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 9A demonstrated the colored marble by using the viscous adhesion of the oxide film to adhere to the phosphor, which revealed that there is nothing adhesion between the liquid metal core (without oxidized part) and the phosphor. [130,131] By respectively coated PTFE and graphene powder on the surface to obtain an anti-oxidation film, the mechanical and conductive properties of RTLMs were reinforced in Figure 9B. [124,129] WO 3 powders adhered to the liquid metal marbles by oxidized wetting are other typical mobile marbles driven by ultraviolet light.…”
Section: Preparation Strategies Between Non-metallic Particles and Rtlmsmentioning
confidence: 99%